The Epistemology of Dissent: Ritual, Counter-Memory, and Hermeneutic Sovereignty among Shi'a Muslims in Garut, Indonesia - Hani Hanifah; Asep Burhanuddin (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2026)
This article advances the thesis that the distinctive ritual practices of Indonesia’s Shi’a Muslim communities tawassul (intercessory supplication through the Ahl al-Bayt), the commemoration of Ashura (10 Muharram), and the commemoration of Ghadir Khum (18 Dhu al-Hijja) function not primarily as expressions of devotional piety but as epistemological operations through which a minority community constructs and defends its hermeneutic sovereignty against majoritarian pressure. Drawing on phenomenological hermeneutics (Ricoeur), Shi’a Islamic philosophy (Corbin, Mulla Sadra), and the theory of corporeal counter-memory (Connerton), this article analyzes ethnographic data from the Majelis Tahlil dan Shalawat community in Ciparay, Garut Regency, West Java. Three key propositions are developed: tawassul enacts an ontological hierarchy of being grounded in Mulla Sadra’s tashkik al-wujud; Ashura operates as a mechanism of corporeal counter-memory that transmits a counter-historiography against the Sunni majoritarian narrative; and Ghadir Khum functions as a performative speech act (in Austin’s sense) that renews the community’s claim to an epistemic lineage running from the Prophet through the Ahl al-Bayt. The article argues that the Glock-Stark religiosity framework dominant in Indonesian Islamic studies is structurally inadequate to capture this epistemological dimension, given its Protestant-derived belief-first assumption. It further argues that Indonesia’s religious tolerance discourse requires reconceptualization beyond equal recognition of devotion toward acknowledgment of minority epistemic sovereignty in the sense theorized by Miranda Fricker.